2016
DOI: 10.1155/2016/5187061
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Thyroid Disorders and Inflammatory Bowel Disease: A Literature Review

Abstract: The aim of this report was to review and summarize the literature on cases of concomitant inflammatory bowel disease (IBD) and thyroid diseases. We included the following previous case reports of concomitant IBD and thyroid diseases: 16 cases of ulcerative colitis (UC) and Graves' disease (GD), 3 cases of Crohn's disease (CD) and GD, 10 cases of CD and Hashimoto's thyroiditis (HT), 4 cases of IBD and subacute thyroiditis (SAT) or SAT-like symptoms, and 13 cases of IBD (12/13 cases were CD) and amyloid goiter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“…The prevalence of another immune‐mediated disease in our cohort was 21%. This is comparable to the prevalence identified in other cohorts and supports an increase in the frequency of these diseases in those with IBD as has been demonstrated by several previous studies . The most common immune‐mediated diseases in our cohort were asthma and psoriasis, both of which have been commonly reported in other cohorts as well and to occur at an increased frequency in those with IBD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of another immune‐mediated disease in our cohort was 21%. This is comparable to the prevalence identified in other cohorts and supports an increase in the frequency of these diseases in those with IBD as has been demonstrated by several previous studies . The most common immune‐mediated diseases in our cohort were asthma and psoriasis, both of which have been commonly reported in other cohorts as well and to occur at an increased frequency in those with IBD.…”
Section: Discussionsupporting
confidence: 92%
“…The overlap may also be due to common environmental risk factors such as smoking that is known to modulate risk for several immune‐mediated diseases including CD, rheumatoid arthritis, and psoriasis. While many studies have investigated the prevalence of concomitant immune‐mediated diseases in IBD, few have looked at the impact this has on disease course and it is not known whether affected individuals who have multiple immune‐mediated diseases have a more aggressive course of these diseases by virtue of a greater genetic burden . Most of the data investigating this topic has been on the co‐existence of primary sclerosing cholangitis and IBD with rare scattered reports on coeliac disease and thyroid disorders .…”
Section: Introductionmentioning
confidence: 99%
“…For example, one review study by Shizuma concluded that there might be no obvious differences in the prevalences of thyroid dysfunction (hyper-or hypothyroidism) between patients with inflammatory bowel disease (IBD) and general populations. 7 Another large-scale epidemiological study by Casella et al (162 UC patients and 5721 controls) also concluded that the incidence of thyroid dysfunction in the general population was significantly higher than that found in the UC patient cohort (7.4% vs 2.5%). 16 Therefore, the association between hyperthyroidism and UC has remained inconclusive to date.…”
Section: Introductionmentioning
confidence: 94%
“…also reported that the prevalence of thyrotoxicosis in UC patients was significantly higher compared to that in controls (3.7% vs 0.8%) in 1975. Since then, only some case reports or reviews have attempted to explore this association . However, although the majority of such reports indicated an association of hyperthyroidism with UC, some studies failed to observe such an association.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation